The relationship of parent-child interaction on the academic stress among early adolescents - Puspita, Luh Mira; Uttamaningdyah, Ni Putu Aryadewi; Utami, Kadek Cahya; Devi, Ni Luh Putu Shinta (KHD-Production, 2025)
Early adolescents are particularly susceptible to academic stress, which can adversely impact their mental well-being in educational settings. Parental influence plays a significant role in contributing to this stress. This study examines the relationship between parent-child interactions and academic stress among early adolescents in Denpasar City. The research was conducted at SD Negeri 8 Padangsambian, employing a quantitative correlational methodology with a sample size of 77 respondents selected through total sampling. The study utilized the Parent-Child Interaction Questionnaire (PACHIQ-R) and the Educational Stress Scale for Adolescents (ESSA) as measurement instruments. The Pearson correlation test was applied, yielding a p-value of 0.419 (p<0.05), indicating that the null hypothesis could not be rejected. Consequently, no significant relationship was found between parent-child interaction and academic stress in early adolescents in Denpasar City. It is recommended that schools implement learning evaluations and offer counseling sessions to mitigate academic stress and assess students' conditions.